EKSPLORASI ETNOMATEMATIKA PADA BENTUK ANYAMAN ENDE - Yasinta Yenita Dhiki; Maria Goreti Diciloam Bantas (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
The purpose of this study is to explore the ethnomathematical concepts contained in the woven form of the Ende tribe. This type of research is exploratory research using an ethnographic approach. The subjects in this study were woven gedek and khidhe craftsmen, mothers who used to make plaits in Rewa Rangga Village, Ende Regency. The instruments in this research are field study interviews and documents. Data analysis used is a triangulation technique. The results showed that there were geometric shapes in woven shapes and motifs. Geometric shapes that are explored are building spaces: beams; flat shapes: circles, regular hexagons, rectangles, and rhombus.